Standing wave performance test of IDT-SAW transducer prepared by silk-screen printing - Ziping Wang; Zhengxuan Jiang; Liangbin Chen; Yefei Li; Meixia Li; Shaohan Wang (AIP Advances, 2018)
With the advantages of high performance and low loss, interdigital surface acoustic wave (IDT-SAW) transducers are widely used in the fields of nondestructive testing, communication and broadcasting. The production, performance and application of surface acoustic wave (SAW) actuators has become a research hotspot. Based on the basic principle of SAW, an IDT-SAW transducer is designed and fabricated using silk-screen printing in this work. The experiment results show that in terms of SAW performance, the fabricated IDT-SAW transducer can generate standing wave fields comparable to those generated using traditional fabrication methods. The resonant frequency response of the IDT-SAW transducer and SAW attenuation coefficient were obtained by experiments. It has provided a method to test the transducer sensing performance by using fabricated IDT-SAW transducer.